Phase I/II results of ceralasertib as monotherapy or in combination with acalabrutinib in high-risk relapsed/refractory chronic lymphocytic leukemia - Wojciech Jurczak; Nagah Elmusharaf; Christopher P. Fox; William Townsend; Amanda G. Paulovich; Jeffrey R. Whiteaker; Fanny Krantz; Chuan-Chuan Wun; Graeme Parr; Shringi Sharma; Veerendra Munugalavadla; Richa Manwani; et al. (Therapeutic Advances in Hematology, 2023)
Background: Patients with relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL) have limited treatment options. Ceralasertib, a selective ataxia telangiectasia and Rad-3-related protein (ATR) inhibitor, demonstrated synergistic preclinical activity with a Bruton tyrosine kinase (BTK) inhibitor in TP53 - and ATM -defective CLL cells. Acalabrutinib is a selective BTK inhibitor approved for treatment of CLL. Objectives: To evaluate ceralasertib ± acalabrutinib in R/R CLL. Design: Nonrandomized, open-label phase I/II study. Methods: In arm A, patients received ceralasertib monotherapy 160 mg twice daily (BID) continuously (cohort 1) or 2 weeks on/2 weeks off (cohort 2). In arm B, patients received acalabrutinib 100 mg BID continuously (cycle 1), followed by combination treatment with ceralasertib 160 mg BID 1 week on/3 weeks off from cycle 2. Co-primary objectives were safety and pharmacokinetics. Efficacy was a secondary objective. Results: Eleven patients were treated [arm A, n  = 8 (cohort 1, n  = 5; cohort 2, n  = 3); arm B, n  = 3 (acalabrutinib plus ceralasertib, n  = 2; acalabrutinib only, n  = 1)]. Median duration of exposure was 3.5 and 7.2 months for ceralasertib in arms A and B, respectively, and 15.9 months for acalabrutinib in arm B. Most common grade ⩾3 treatment-emergent adverse events (TEAEs) in arm A were anemia (75%) and thrombocytopenia (63%), with four dose-limiting toxicities (DLTs) of grade 4 thrombocytopenia. No grade ⩾3 TEAEs or DLTs occurred in arm B. Ceralasertib plasma concentrations were similar when administered as monotherapy or in combination. At median follow-up of 15.1 months in arm A, no responses were observed, median progression-free survival (PFS) was 3.8 months, and median overall survival (OS) was 16.9 months. At median follow-up of 17.2 months in arm B, overall response rate was 100%, and median PFS and OS were not reached. Conclusion: Ceralasertib alone showed limited clinical benefit. Acalabrutinib plus ceralasertib was tolerable with preliminary activity in patients with R/R CLL, though findings are inconclusive due to small sample size. Registration: NCT03328273